1983
DOI: 10.1002/cjce.5450610502
|View full text |Cite
|
Sign up to set email alerts
|

Film thickness in horizontal annular flow

Abstract: Film thickness in horizontal annular flow in small diameter pipes (8‐12 mm) was measured as a function of circumferential position. In addition a simple analytical model for the prediction of the film thickness at the top and bottom of the pipe is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 4 publications
1
11
0
1
Order By: Relevance
“…For all regimes studied, the liquid film holdup was calculated as the cross-sectional area of the liquid film divided by the cross-section of the pipe (as defined by Luninski et al, 1983) …”
Section: Liquid Film Holdupmentioning
confidence: 99%
See 1 more Smart Citation
“…For all regimes studied, the liquid film holdup was calculated as the cross-sectional area of the liquid film divided by the cross-section of the pipe (as defined by Luninski et al, 1983) …”
Section: Liquid Film Holdupmentioning
confidence: 99%
“…Badie et al (2000) measured the film thickness and liquid film holdup in a 78 mm diameter tube using a gamma densitometer system. Luninski et al (1983) determined the film thickness in a 8.15 mm diameter pipe by measuring the resistance of the film. They compared the results with a new model proposed, and calculated theoretically the liquid film holdup.…”
Section: Introductionmentioning
confidence: 99%
“…In order to compare the present δ data with those by other investigators, we conducted a literature survey, and found the data by Luninski et al (3) in water-air horizontal flows at room temperature and at atmospheric condition. In their original paper, the δ data are plotted against j G with j L as a parameter.…”
Section: Mean Liquid Film Thickness In Annular Flowmentioning
confidence: 99%
“…However, the conventional ones smaller than about 12 mm i.d. are usually referred to as "small diameter pipes or tubes" by, say, Barnea et al (2) , Luninski et al (3) , Mishima and Hibiki (4) and Chen et al (5) . The flow in such pipes appears in various cooling devices because they are downsizing.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method that also takes advantage of difference in electrical properties of liquids and gases is based on either capacitance or resistance probes similar to those used in wave height measurements in laboratory wave tanks. These probes consist of a single or of a pair of thin parallel wires and provide quantitative information about the relative length of wetted part of the wires [5].…”
Section: Introductionmentioning
confidence: 99%